The tree with the golden sap - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Acacia senegal, which produces gum arabic, has suffered greatly from the effects of the drought. This tree with the golden sap (gum arabic) does not thrive in plantations, so the only viable method of restoring it to previous numbers is to protect...